ANALISIS PEMBUATAN MAIN PULLEY YST-REVO DENGAN METODE CETAKAN SAND CASTING DAN FINISHING SHOT BLASTING - Ahcmad Fauzan (Jurnal Teknik dan Science, 2024)
Metal casting is a manufacturing process that involves melting metal and pouring it into a mold cavity. This process can be used to create complex shapes, such as the main pulley for hand tractors, specifically the YTS-Revo model. The aim of this study is to understand the production process and the raw materials used, namely gray cast iron, due to its high fluidity and low shrinkage, as well as its excellent damping capacity. The molding method employed by PT. Mitra Rekatama Mandiri is sand casting, where the sand used can be reused multiple times. The production of the main pulley YTS-Revo begins with the creation of a mold using a replica pattern to form a cavity. Next, the raw materials, including cast iron (steel scrap, recycled scrap, and chips), silicon, carbon charcoal, and slag remover, are melted until reaching a temperature of 1300°C. The molten iron is then poured into the mold, followed by cooling and solidification. After the mold is dismantled, the product is cleaned using a shot blasting machine. The machining process involves threading the pulley using a conventional lathe. The final step is finishing, where the product is soaked in gasoline to prevent rust, making it ready for market.